REVITALIZATION OF EDUCATION TO IMPROVE QUALITY ISLAMIC BOARDING SCHOOL EDUCATION - Jumadi; Abdul Latief Arung Arafah; Siti Patimah; Nurul Hidayati Murtafiah (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
Pesantren is an educational institution that has provided gold ink to the history of this country. Islamic boarding schools have contributed to the struggle to liberate Indonesia from Dutch colonialism, and have become part of educating the nation's children, especially in terms of character formation, so along with the times, revitalization in the field of education in the world of Islamic boarding schools is a necessity. The revitalization referred to is in the context of improving the quality of education so that the role and function in society and the state increase.